Experimental and numerical seismic assessment of non-ductile reinforced concrete (RC) columns strengthened with glass fiber reinforced polymer (GFRP) - Rodsin, Kittipoom; Mehmood, Tahir; Kolozvari, Kristijan; Nawaz, Adnan; Samiullah, Qazi; Parichatprecha, Rattapoohm (My University, 2022)
This study presents an experimental and numerical seismic evaluation of non-ductile reinforced concrete (RC) columns strengthened with glass fiber reinforced polymer (GFRP). Three RC column specimens exhibiting three different modes of failure, flexure, flexure-shear, and shear, were strengthened with locally available, inexpensive GFRP sheets and subjected to reversed cyclic loading. The results showed that GFRP sheets not only enhanced the ductility capacity of non-ductile RC columns but also helped to shift the undesirable shear and flexure-shear mode of failure to a more favorable flexural mode. A numerical model based on the multiple-vertical-line-element-model was also proposed and implemented in OpenSees to simulate the experimentally tested specimens. This simple yet robust model was successful in predicting the force–deformation response, including strength degradation of the tested specimens.
Keywords: Flexure-shear; GFRP; MVLEM; OpenSees; Shear